Borrower Financial Literacy and Credit Decision Rationality Amongst People who Take Loans from Money Lenders in the Major Urban Areas of Uganda - Mujabi, Shafic; Rulangaranga, Donatus Mugisha; Kitui, Geofrey Mayoka; Kehbuma, Langmia (Archives of Business Research, 2022)
This research study was carried out to establish the relationship between financial literacy and credit decision rationality amongst people who take loans from money lenders in the major urban areas of Uganda. Focusing on the relationship was based on the need to establish whether credit decision rationality of these borrowers was based on their level of financial literacy. The concept of financial literacy was conceptualized by assessing the three key measures of financial literacy;- financial knowledge, financial skills, and financial behavior. Based on this conceptualization, three hypotheses were formulated and tested. The people that take loans from money lenders in the major urban areas of Uganda were considered to form the population of the study. A maximum sample of 385 [as recommended by Krejcie and Morgan (1970)] was selected. A 93% response rate was realized. Correlation and regression analyses were carried out to test the hypotheses. The results indicated that financial literacy has a 19.4% influence on changes in credit decision rationality of people that take loans from money lenders in the major urban areas of Uganda. Additionally, the results indicated that financial behavior has the highest significant association with and influence on credit decision rationality, followed by financial skills. Financial knowledge also has influence on credit decision rationality though the influence is not statistically significant. Based on these results, it is recommended that, financial literacy be enhanced amongst Ugandans, especially those that tend to take loans from money lenders. In the process of enhancing financial literacy, there is need to put emphasis on attaining or instilling appropriate financial behavior that can enable a person reduce his or her debt burden.